Application of next-generation sequencing to identify different pathogens - Nafea, Aljuboori M.; Wang, Yuer; Wang, Duanyang; Salama, Ahmed M.; Aziz, Manal A.; Xu, Shan; Tong, Yigang (Frontiers in Microbiology, 2024)
Early and precise detection and identification of various pathogens are essential for epidemiological monitoring, disease management, and reducing the prevalence of clinical infectious diseases. Currently available pathogen detection techniques, which include mass spectrometry, biochemical tests (metabolic fingerprinting), molecular testing (usually PCR), and culture-based procedures, are limited in application and are time-consuming. Next generation sequencing (NGS) has emerged as an essential technology for identifying clinical pathogens.NGS is a cutting-edge DNA sequencing method with high throughput that can create massive volumes of sequences with a wide range of potential uses in research and diagnostic settings.NGS presents a revolutionary way to overcome the issues with fast speed, potential application in unknown pathogen detection, improved sensitivity, and efficient data interpretation. In this review, we introduce NGS technology in detail, summarizes the application of NGS in that identification of different pathogens, including bacteria, fungi, and viruses, and analyse the challenges and outlook for using NGS to identify clinical pathogens. Thus, this work provides a theoretical basis for NGS studies and provides evidence to support the application of NGS in distinguishing various clinical pathogens.